Effects of Outcomes and Random Arbitration on Emotions in a Competitive Gambling Task - Bediou, Benoit; Mohri, Christelle; Lack, Jeremy; Sander, David (Frontiers in Psychology, 2011)
The affective events theory proposes that the evaluation of distributive and procedural justice map onto primary and secondary appraisal sequence, respectively. However, self-serving biases suggest that one dimension (outcome favorability) can bias the other (procedural fairness). For the first time, we investigated the emotional correlates of this phenomenon. Participants performed a choice task between pairs of competing gambles against a virtual opponent. Conflicts (when the participant selected the same gamble as his virtual opponent) were resolved by a neutral arbitrator who either confirmed the participant’s choice (“pro-self”) or attributed his gamble to the virtual opponent (“pro-competitor”). Trials in which the participant and his virtual opponent selected different gambles (“no-conflict”) served as a control condition. Emotional reactions to the outcomes of the gambles were measured using self-reports, skin conductance responses and facial electromyography (zygomaticus, corrugator and frontalis).In no-conflict trials, effects of counterfactual thinking and social comparison resulted in (i) increased happiness as well as SCR and zygomaticus activity for wins compared to losses (valence effect) and for high compared to low gains (magnitude effect), and (ii) increased anger, regret, disappointment and envy for losses compared to wins (valence effect). More importantly, compared to no-conflict trials and to pro-self awards with similar outcomes, pro-competitor awards increased subjective reports of anger for unfavorable outcomes, and increased happiness and guilt for favorable outcomes. Although the outcomes were independent from the arbitrators’ decisions, and both the arbitrators’ decisions and the outcomes were kept equally likely, individuals tended to attribute their outcomes to unfair arbitrators, reacting emotionally, especially when the modification of their initial choice for a gamble led to a negative outcome.